The analysis of the BAS OH band in zeolites - Rubes, Miroslav; Trachta, Michal; Vaculík, Jan; Bulánek, Roman; Bludsky, Ota (Elsevier Science BV, 2022)
The zeolite frameworks (FER, TON, CHA, and IFR) with a large diversity of the IR band shapes in the OH stretching region were investigated by combined use of FT-IR spectroscopy and DFT calculations. The analysis of various isolated Brunsted acid sites was performed with a model based on Boltzmann weighted relative energies and OH frequencies obtained by the omega/r correlation method. This approach has recently been used to reveal the non-statistical incorporation of aluminum into the H-MOR framework. The model correctly predicts the band shapes of H-FER and H-TON zeolites in the free OH region of the FT-IR spectra. For H-CHA and H-IFR, however, the mutual BAS interactions cannot be ignored even for high Si/Al ratios, which renders the concept of isolated BAS inadequate. Thus, the periodic calculations of adsorption and catalytic properties of zeotype frameworks should always be carried out with extended models mimicking real heteroatom distribution in these materials.
Analýza BAS OH vazeb v zeolitech
Keywords: acidic zeolites; Ab initio calculations; IR spectra; kyselé zeolity; ab inition výpočtyů IR spektra